Development of temperature regime of storage of frozen black currants - Osokina, Nina; Kostetska, Kateryna; Herasymchuk, Olena; Tkachenko, Hennadii; Podpriatov, Hryhorii; Pusik, Ludmila; Falendysh, Nataliy; Bobel, Inna; Belinska, Kristina (Eastern-European Journal of Enterprise Technologies, 2021)
The process of ice formation in the pericarp of black currant depends on the pomological variety, the degree of ripeness of the fruit, and the method of freezing. During the slow and fast freezing of black currant, four ranges of fruit cooling temperatures are distinguished: 1) from the temperature of the fruit to the temperature of initiation of ice formation; 2) from the temperature of the front (initiation) of ice formation to the lowest possible temperature of the fetal mesocarp; 3) from the lowest possible temperature of the mesocarp to the lowest temperature of the fetal endocarp; 4) from the lowest possible endocarp temperature to fetal freezing temperature. Fast freezing boosts cooling, freezing and freezing from 37 min. (slow) up to 5.6 min. due to a halving of the temperature of initiation of ice formation, an increase of 1.3 times in the rate of heat extraction and an increase in the freezing temperature from –22...–24 °С (slow) to –20.8 °С. It is scientifically substantiated that the temperatures of freezing fruits significantly change the general existing recommendations (not higher than –18 °С) regarding the storage conditions of black currant fruits: with quick freezing, not higher than –21 °С, with slow freezing, not higher than –24 °С. The formation of the properties of black currant occurs during the growing season under various agro-climatic conditions and affects the parameters of ice formation indicators. The marketable condition, quality and organoleptic characteristics of black currant fruits depend on the method of freezing. The advantages of fast freezing of black currant fruits in a quick-freezing chamber with forced air circulation at a speed of 1.5–2.5 m/s at a temperature of –30...–32 °С in comparison with slow freezing in freezers at a temperature of –20 have been established. ..– 22 °С.